(3eLeY GdMce GdSdWGfjg hefHY GdeYGQa GdQhMGfjgs - (3CMeO Hf GdTQja CTQa GdSjO eMeO GdMSjfjs; (3GdSeQbfOj , TeS GdOjf eMeO Hf GTQa GdMSjfj GdSeQbfOj,J (B690 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi fUH dQajY bUQ GdSYGOI ef GdYde YeGOG hHYO aEf eaGNQ GdYde dG JMUi GPG dYde eWdhH dPGJg eQZhH ajg s
(3BNQgG (B:s
(3Gddge GMTQfG ai ReQJg hCeJfG Ydi eMHJg hGLYdfG ef GdeJHYjf GdfGLjf GdegJOjf s
(3XgQ GSe GdfGSN ai fgGjI GdeNWhW HNW ZjQ hGVMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B39 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B63s
Keywords: (3GdSjGSI hGdGLJeGYs